Capaian pembangunan manusia: analisis komparatif Provinsi Banten, Jawa Barat dan DKI Jakarta - Adriwati Adriwati (Jurnal Good Governance, 2017)
Human development is a development paradigm that puts human (population) as the focus and final target of all development activities, namely the achievement of control over resources (income to achieve decent living), improvement of health status (long life and healthy life) and improve education. To see the success rate of human development, UNDP publishes an indicator of Human Development Index (HDI). This study discusses the achievements of human development that have been pursued by the government. The problem analyzed in this research is the difference of human development achievement in some provincial government in Indonesia. This paper aims to compare the achievements of human development in some provincial governments seen from the achievement of human development index of each province. Research location in Banten Province, West Java and DKI Jakarta.Keywords:Human Development Index, Human Development Achievement